The mediating role of coping in the relationship between perceived health and psychological wellbeing in recurrent urinary tract infection: the rUTI Illness Process Model - Abigail F. Newlands; Melissa L. Kramer; Kayleigh Maxwell; Jessica L. Price; Katherine A. Finlay (Health Psychology and Behavioral Medicine)
Background: Recurrent urinary tract infection (rUTI) is associated with significant symptom and quality of life burden. Given the unique challenges in diagnostics and management, healthcare disillusionment and stigmatisation which distinguish rUTI from other urological conditions, specific identification of the key illness processes experienced by this patient population is required. This study aimed to identify the unique illness processes and perceptions that contribute to quality of life in rUTI, through perceived health status, psychological wellbeing, and coping.Methods: An international sample of adults living with rUTI (N = 389, 96.9% female) completed a cross-sectional survey comprising the following standardised questionnaires: the EuroQoL EQ-5D-5L, Patient Health Questionnaire 9 (PHQ-9), Generalised Anxiety Disorder 7 (GAD-7), Connor-Davidson Resilience Scale–10 (CD-RISC-10), Pain Catastrophising Scale (PCS). Sociodemographic characteristics were also assessed. Structural equation modelling was conducted to identify the underlying constructs which contributed to psychological wellbeing in rUTI, establishing the ‘rUTI Illness Process Model’.Results: The positive relationship between ‘perceived health status’ and ‘psychological wellbeing’ was partially mediated by ‘rUTI coping’, after controlling for the impact of household income and age (p < .001). The model demonstrated a large effect size (R2 = .81) and good local and global fit. Overall, rUTI coping skills, boosted by resilience and weakened by pain catastrophising, contribute to a significant proportion of the positive relationship between perceived health status and psychological wellbeing in rUTI. A uniquely vulnerable patient phenotype emerges from this new research, with patients who are younger and/or of lower socioeconomic status at greater risk of poorer rUTI health outcomes and psychological wellbeing, potentially requiring further support.Conclusions: The rUTI Illness Process Model establishes the crucial need to clinically characterise the individualised illness perceptions and metacognitive strategies held by people living with rUTI, revealing that patient-centred interventions targeting illness perceptions and coping strategies require prioritisation to enhance patient outcomes and the patient experience of living with rUTI.